Contribution of the Fetal Cardiac Axis and V‐Sign Angle in First‐Trimester Screening for Major Cardiac Defects. (12th September 2018) - Zheng, Ming M.; Tang, Hui R.; Zhang, Yan; Ru, Tong; Li, Jie; Xu, Bi Y.; Xu, Yan; Hu, Ya L.
Abstract : Objective: To estimate the potential value of fetal assessment for the cardiac axis (CAx) and V‐sign angle (VSA) in the first trimester in the prediction of fetal major cardiac defects. Methods: A cohort study was conducted from December 2015 to June 2016. Patients with singleton pregnancies and crown‐rump length from 45 to 84 mm were recruited to undergo nuchal translucency sonography. The CAx on the 4‐chamber view and the VSA on the 3‐vessel and trachea view with Doppler mapping were measured. The estimated performance of different combinations of increased fetal nuchal translucency, CAx, and VSA in screening for major cardiac defects was examined. Results: The study population of fetuses included 30 fetuses with major cardiac defects and 1538 normal fetuses. The CAx and VSA were 30° to 60° and 30° to 40°, respectively, according to the 2.5th and 97.5th percentiles in normal fetuses. When cases of isolated septal wall defects and an isolated right aortic arch were excluded, nuchal translucency above the 95th percentile, an abnormal CAx, and an abnormal VSA were observed in 63.3% (19 of 30), 63.3% (19 of 30), and 66.7% (20 of 30) of fetuses with major cardiac defects, respectively, and in 4.6% (71 of 1538), 2.0% (30 of 1538), and 5.6% (86 of 1538) of those without cardiac defects. Either an abnormal CAx or VSA was found in 93.3% (28 of 30) of the fetuses with cardiac defects and in 7.3% (113 of 1538) of those without cardiac defects. Conclusion: Assessment of the CAx and VSA is helpful in defining a population at risk for major cardiac defects in the first trimester.